Correlations of Protein 53 (p53) Expression with the Degree of Tumor Budding in Cervical Carcinoma - Wardana, Ni Komang Sara Kusuma; Armerinayanti, Ni Wayan; Cahyawati, Putu Nita (http://dharmais.co.id/, 2025)
Background: Cervical carcinoma is a malignant tumor that is most often found in the female reproductive system. Persistent Human Papillomavirus (HPV) infection is the most important factor in the development of cervical carcinoma. The E6 and E7 oncoproteins in HPV inhibit the action of p53. As a result, p53 transcription and the apoptosis process are inhibited. Tumor budding has been extensively studied and established as a significant prognostic factor. This study aims to determine the relationship between p53 expression and the degree of tumor budding of cervical carcinoma.Method: This cross-sectional study used 50 paraffin blocks and secondary data from patients diagnosed with cervical carcinoma stored at BaliMed Denpasar Hospital. Paraffin blocks were then subjected to immunohistochemical examination to evaluate p53 expression and HE examination to evaluate the degree of tumor budding. Data analysis was performed using the Spearman test and linear regression test with the SPSS 25 software program. Results: The results showed that thirty-two subjects had low expression of p53, and 62,5% of them had high-grade tumor budding. The p53 expression is lower in cervical cancer with highgrade tumor budding compared with low-grade tumor budding (rs = -0.33). There are significant correlations between p53 expression and the degree of tumor budding in patients with cervical carcinoma (p = 0.018). A total of 50 samples that met the inclusion and exclusion criteria were analyzed. The majority of patients were aged ≤ 50 years (58%) and had squamous cell carcinoma (90%) in the early stage (92%). Low p53 expression was found in 64% of samples. A significant negative correlation was found between p53 expression and tumor budding grade (p = 0.018; r = -0.333), which remained significant in multivariate analysis (p = 0.024; r² = -0.328), indicating that low p53 expression is associated with high-grade tumor budding. Conclusion: The p53 expression was significantly downregulated in cervical carcinoma with highgrade tumor budding. These findings indicate that tumor budding can be considered as a prognostic marker, but further research that sorts HPV dependent and HPV independent cervical carcinomas is needed.